Precipitation Regulates the Assembly Processes of Rare Species in Phytoplankton Communities in River Ecosystems - Enze Xiao; Xiaofeng Liu; Tian Lou; Yimin Zhu; Yiou Wang; Xinxin Lu; Yawen Fan; Xiang Tan; Yan Liu (Diversity)
Phytoplankton communities typically comprise a few dominant species and numerous rare ones, but their responses to seasonal precipitation changes remain poorly understood. To address this knowledge gap, investigations were conducted on the environmental conditions and phytoplankton communities in the Lalin River Basin during the dry and rainy seasons. Structural equation modeling and co-occurrence network analysis were then utilized to explore the assembly processes of dominant and rare phytoplankton communities following a seasonal heavy rainfall event. Our results showed seasonal heavy rainfall events significantly altered the phytoplankton community composition and rare phytoplankton diversity (p < 0.05). Furthermore, the stochastic process was particularly pronounced for rare species (i.e., 4.44%, p < 0.01). Co-occurrence network analysis revealed that increasing precipitation enhances the complexity and stability of phytoplankton ecological networks. Additionally, the relative importance of dominant species decreases, while that of rare species increases. This phenomenon can be described as the seasonal heavy precipitation weakening the so-called “Matthew effect” in the ecosystem. In summary, our results shed light on the phytoplankton ecology of agricultural rivers and reveal how changes in precipitation influence the formation of phytoplankton sub-communities and the structure of their networks.